Medicine and Sport Science 2008
DOI: 10.1159/000134294
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi Exercise and the Improvement of Mental and Physical Health among College Students

Abstract: Tai Chi exercise had positive effects on the self-assessed physical and mental health of college students. Scores on the MHD appeared to be particularly sensitive to change. Colleges/universities might consider offering Tai Chi as a component of their ongoing physical activity programs available to students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 12 publications
1
19
1
4
Order By: Relevance
“…Several lines of evidence show that the exercises involving stretching exercise incorporate with breathing practice such as Yoga and Taichi (Madanmohan et al, 2008;Wang, 2008) provide physical health benefit including cardiorespiratory function, muscle strength and posture control (Lee et al, 2009;Tran et al, 2001;Tsang and Hui-Chan, 2004). Moreover, they can also enhance antioxidant enzymes activities such as Superoxide Dismutase (SOD) and Glutathione Peroxidase (GSH-Px) while decrease Malondialdehyde (MDA) level (Agte et al, 2011;Hegde et al, 2011;Goon et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence show that the exercises involving stretching exercise incorporate with breathing practice such as Yoga and Taichi (Madanmohan et al, 2008;Wang, 2008) provide physical health benefit including cardiorespiratory function, muscle strength and posture control (Lee et al, 2009;Tran et al, 2001;Tsang and Hui-Chan, 2004). Moreover, they can also enhance antioxidant enzymes activities such as Superoxide Dismutase (SOD) and Glutathione Peroxidase (GSH-Px) while decrease Malondialdehyde (MDA) level (Agte et al, 2011;Hegde et al, 2011;Goon et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Es por esto que, las PMI, tanto psicomotrices como de cooperación, entrañan repercusiones positivas para las personas; ya que se mejora el estado de ánimo al reducirse la ansiedad (Wayment et al, 2011), el estrés (Delgado, et al 2010;Eastman-Mueller, et al 2013;Newsome et al, 2012), la depresión o la fatiga (Delgado, et al 2010) y verse amplificados el bienestar subjetivo (Li, 2012;Ross, Friedmann, Bevan, y Thomas, 2013;Wang, 2008), la vitalidad, la resiliencia interior (Wayment et al, 2011), la autocompasión (arias, et al, 2006;Newsome et al, 2012), la integración social (Yao et al 2008) y las emociones positivas (Rovira et al, en prensa).…”
Section: Los Beneficios De Las Prácticas Motrices Introyectivasunclassified
“…Hacer frente a las emociones negativas y tener niveles de ansiedad y tensión más bajos parece propio de aquellas personas habituadas a la práctica deportiva regular (Reigal, Márquez, Videra, Martín y Ruiz, 2013;Taylor-Piliae et al, 2006) pero lo que aporta de particular este estudio es la constatación de los efectos positivos que sobre el bienestar general tiene la ejercitación en PMI (Lagardera, 2007;Li, 2012;Rovira, 2010;Rovira et al, en prensa;Wang, 2008).…”
Section: Práctica Motriz Introyectiva Y Autorregulación Emocionalunclassified
“…More importantly, metabolic syndrome risk is increased with weight gain in young adults, regardless of initial weight status [7]. Although research has demonstrated that weight loss programs are effective in middle-aged adults [8], these programs may not translate to younger populations such as college students, who deal with typical barriers such as demands on time and financial issues, but also have additional challenges such as peer and academic pressure [9][10][11]. Yet, recent data from the CARDIA study [12] emphasize the need for interventions promoting the adoption of healthy lifestyle behaviors, including achievement and maintenance of healthy weight status through appropriate dietary intake and physical activity levels.…”
Section: Introductionmentioning
confidence: 99%